“When Do I Cross the Street?” Roberta’s Guilty Reflection - Irene A. Lietz (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Following a student’s evolving attitudes on race issues through her undergraduate years, a researcher concludes that a critical pedagogy can have long-term effects on student and instructor alike.